Nowe elementy w biografiach zawodowych młodych Polaków. Zarys problematyki = New Elements in Professional Biographies of Young Poles - Outline - Róg-Ilnicka, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to answer the question if and to what extent the young generation of Poles has accepted the models of professional career which include qualities characteristic for post-modern labour market, i.e. unemployment episodes, incomplete and insecure employment and unusual forms of work.
Keywords: młodzież; młodzi dorośli; preferencje zawodowe; bezrobocie; Lubuskie